Caking Phenomena During Pilot-Scale Crystallization of Dextrose Monohydrate - Harsojo Harsojo; Eriawan Rismana; Bayu Mahdi Kartika (Universitas Gadjah Mada, 2021)
Dextrose Monohydrate (DMH) is a bulk chemical used in the food, beverage, and pharmaceutical industries. The caking often appeared in the crystallization of DMH. Caking is an agglomeration that can affect the product quality of DMH and is dependent on the type of impeller. This study aimed to determine the type of impeller to avoid the caking during the DMH crystallization and identify the DMH caking. The results showed that caking did not occur on the helical ribbon and anchor impeller, while caking appeared on the Rushton turbine impeller. Computational fluid mechanics (CFD) analysis showed that caking occurs due to uneven homogeneity of stirring. Fourier transform infrared (FTIR) and X-ray diffraction (XRD) studies showed that DMH caking and non-caking had the same peak pattern. Meanwhile, optical microscope and scanning electron microscope (SEM) analysis showed that the DMH caking seen agglomerate. Density analysis showed that DMH with caking was 1.257–1.350 kg/L, while the non-caking was 0.504–0.780 kg/L. Caking phenomena during the DMH crystallization can be avoided by using a helical ribbon and anchor impeller. FTIR and XRD analysis cannot be used to identify DMH caking products; meanwhile, optical microscope, SEM, and density analyzes can be used to identify DMH caking products.